Evidence of impaired microvascular dilatation in preterms with acute respiratory distress syndrome. (15th August 2017) - Troiani, Stefania; Cardona, Andrea; Milioni, Maddalena; Monacelli, Debora; Verrotti, Alberto; Gehring, Marta; Ambrosio, Giuseppe
Abstract: Background: Evaluating microcirculatory function in severely ill neonates is a relevant, unmet clinical need. Inappropriate peripheral microvascular vasodilatation is thought to contribute to cardiovascular alterations in preterm infants with acute respiratory distress syndrome (ARDS). We directly evaluated microcirculatory function in preterms with ARDS. Methods: Peripheral microvascular function was assessed in 50 newborns, divided in three groups: preterms with ARDS; at-term newborns with mild-moderate congenital cardiac disease (Cardio group); healthy controls. Skin microvascular perfusion was assessed using an operator-independent, laser-Doppler camera, under basal conditions and during post-ischemic hyperemia, allowing objective quantification of microcirculatory flow reserve (MFR). Results: At baseline, perfusion was similar among the three groups. During post-ischemic phase, microcirculatory perfusion significantly increased in controls compared to baseline (baseline perfusion units [PU] 3.65 ± 1.8 to 4.59 ± 2.1 during hyperemia; p for trend = 0.041), whereas in ARDS group perfusion tended to decrease. Comparing results across groups, ARDS showed lower values compared to either controls or Cardio groups ( p  < 0.05). Controls, and to a lesser extent Cardio group, showed recruitable MFR (1.78 ± 1.13 and 1.19 ± 0.30 in controls and Cardio group, respectively). MFR was absent in ARDS (0.88 ± 0.48; p  < 0.05), documenting impaired microcirculatory response. Conclusion: We demonstrate that it is possible to assess, non-invasively and quantitatively, vasodilator response of skin microcirculation to physiological stimuli in neonates. We also documented that microvascular vasodilation is impaired in preterms with ARDS. Highlights: Evaluating microcirculatory function in severely ill infants is a relevant, unmet clinical need. Techniques directly assessing microcirculatory function have practical limitations, precluding use in neonates. We assessed non-invasively, vasodilator response of microcirculation in neonates. We demonstrated that skin microvascular vasodilation is impaired in preterms with ARDS.